2012
DOI: 10.1017/s1743921312024118
|View full text |Cite
|
Sign up to set email alerts
|

Unified description of dense matter in neutron stars and magnetars

Abstract: Abstract.We have recently developed a set of equations of state based on the nuclear energy density functional theory providing a unified description of the different regions constituting the interior of neutron stars and magnetars. The nuclear functionals, which were constructed from generalized Skyrme effective nucleon-nucleon interactions, yield not only an excellent fit to essentially all experimental atomic mass data but were also constrained to reproduce the neutron-matter equation of state as obtained f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…( 2). When comparing our new results for the composition with the ones [8,10] obtained using the 2012 AME [29], we notice several differences. First of all, the pressure between some adjacent crustal layers and their mean baryon densities are slightly shifted due to refined mass measurements.…”
Section: A Outer Crustmentioning
confidence: 72%
See 1 more Smart Citation
“…( 2). When comparing our new results for the composition with the ones [8,10] obtained using the 2012 AME [29], we notice several differences. First of all, the pressure between some adjacent crustal layers and their mean baryon densities are slightly shifted due to refined mass measurements.…”
Section: A Outer Crustmentioning
confidence: 72%
“…The effects of a high magnetic field on a magnetar are most prominent in the outer crust, which consists of a succession of different strata made of atomic nuclei with proton number Z and mass number A in a charge-compensating electron background. We have previously shown that the composition and the equation of state in this region can be drastically modified due to Landau-Rabi quantization of electron motion [7][8][9][10] (see also Ref. [11] for a general review).…”
Section: Introductionmentioning
confidence: 99%
“…For the "low" magnetic fields B 1 prevailing in most neutron stars, the internal constitution of their outer crust is essentially the same as in the absence of magnetic fields except possibly near the stellar surface, as discussed in Section 2.3. For higher magnetic fields B 1 as measured in SGRs, AXPs, and some radio pulsars, the composition is found to depend on the magnetic field [41,42,90,91,92]. In particular, the maximum baryon number density nmax up to which a nuclide (A 1 , Z 1 ) is present exhibit typical quantum oscillations as a function of the magnetic field strength [65,68,93].…”
Section: Highly Magnetised Neutron Starsmentioning
confidence: 99%